Terapia systemowa rodzin jako jeden ze sposobów rozwiązywania problemów dzieci i młodzieży - Grzesiak, Emilia (Wydawnictwo Naukowe EDUsfera. Ewa Jurczyk-Romanowska, 2021)
This article deals with the issue of systematic family therapy, which is one of the currently used forms of family support in difficult and crisis situations. The publication introduces this issue, explains the goals and general assumptions of the approach, with particular emphasis on the perspective of children and adolescents.
Keywords: therapy; system; family; systemic family therapy